The use of pigment “fingerprints” in the study of harmful algal blooms - Bustillos-Guzmán, J. (2004)
Along the Mexican coast, harmful algae blooms (HAB) have become more frequent, and therefore, there is an urgent need to establish monitoring programs to avoid the undesired consequences of HAB in human and natural ecosystems. In this work, we analyzed the pigment signatures and the species composition from phytoplankton samples to evaluate the utility of the specific pigment “fingerprints” in HAB monitoring programs. Vertical profiles from a coastal lagoon and temporal samples of a red tide occurring in a shrimp-culture pond and in a coastal zone were taken into consideration. Between 76% and 84% of dinoflagellate and diatom cell density was explained by their specific signature variation, in both vertical and temporal samples. Only the variation of zeaxanthin and the cyanobacteria Anabaena sp. showed a poor relationship, probably from difficulties in counting other cyanobacteria present in the samples examined with the microscopic method. These results suggest that inclusion of pigment analysis in the study and monitoring programs dealing with harmful algae would be very useful